Sharia Digital Innovation Trend: OJK Involvement Changes Indonesia's Islamic Finance Landscape - Friska Najwa; Cory Vidiati; Raisalam D. Angoy; Heru Cahyono; abu Lubaba (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2024)
This paper explains that Islamic digital finance experiences a mechanical shift in implementation when there is financial technology innovation. A development strategy in line with Islamic law is essential to ensure that this innovation is not just an idea, but can also be implemented effectively according to the community's needs. Using a qualitative approach and secondary data as study material developed, compiled and concluded. The findings are that the Financial Services Authority (OJK) has shown commitment to strengthening the Islamic fintech ecosystem through various programs, such as Gebyar Safari Ramadhan and Ijtima' Sanawi, which have contributed to the Global Islamic Fintech Indicator ranking. In general, they have been unable to boost financial literacy and Islamic financial inclusion in the wider community. Another finding is the importance of developing Islamic digital financial innovations that are more inclusive and responsive to the needs of the halal food sector through the development of inclusive Islamic financial products and services, such as Sharia-based crowdfunding platforms and halal e-commerce with Sharia payments. The contribution of the findings is expected to map the weaknesses into the strengths of the global Islamic economy.